Enzymatic regulation of skeletal muscle oxygen transport: novel roles for neuronal nitric oxide synthase - Copp, Steven Wesley (Kansas State University, 2013)
Nitric oxide (NO) is synthesized via distinct NO synthase (NOS) enzymes and constitutes an essential cardiovascular signaling molecule. Whereas important vasomotor contributions of endothelial NOS (eNOS) have been well-described, the specific vasomotor contributions of nNOS-derived NO in healthy subjects during exercise are unknown. The purpose of this dissertation is to test the global hypothesis that nNOS-derived NO is a critical regulator of exercising skeletal muscle vascular control. Specifically, we utilized the selective nNOS inhibitor S-methyl-L-thiocitrulline (SMTC) to investigate the effects of nNOS-derived NO on skeletal muscle vascular function within established rodent models of exercise performance. The first investigation (Chapter 2) identifies that nNOS inhibition with SMTC increases mean arterial pressure (MAP) and reduces rat hindlimb skeletal muscle blood flow at rest whereas there are no effects during low-speed (20 m/min) treadmill running. In Chapter 3 it is reported that nNOS inhibition with SMTC reduces blood flow during high-speed treadmill running (>50 m/min) with the greatest relative effects found in highly glycolytic fast-twitch muscles and muscle parts. Chapter 4 demonstrates that nNOS-derived NO modulates contracting skeletal muscle blood flow (increases), O2 consumption (VO2, increases), and force production (decreases) in the rat spinotrapezius muscle and thus impacts the microvascular O2 delivery-VO2 ratio (which sets the microvascular partial pressure of O2, PO2mv, and represents the pressure head that drives capillary-myocyte O2 diffusion). In Chapter 5 we report that systemic administration of the selective nNOS inhibitor SMTC does not impact lumbar sympathetic nerve discharge. This reveals that the SMTC-induced peripheral vascular effects described herein reflect peripheral nNOS-derived NO signaling as opposed to centrally-derived regulation. In conclusion, nNOS-derived NO exerts exercise-intensity and muscle fiber-type selective peripheral vascular effects during whole-body locomotor exercise. In addition, nNOS-derived NO modulates skeletal muscle contractile and metabolic function and, therefore, impacts the skeletal muscle PO2mv. These data identify novel integrated roles for nNOS-derived NO within healthy skeletal muscle and have important implications for populations associated with reduced NO bioavailability and/or impaired nNOS structure and/or function specifically (e.g., muscular dystrophy, chronic heart failure, advanced age, etc.).
Keywords: Skeletal muscle; Nitric oxide; Blood flow; Vasodilation; Exercise; Physiology (0719)